Motion Analysis of Kinetic Impact Projectiles for Physics Education in Real Context - Hernandez-Silva, C (Institute of Physics, 2021)
The article presents a proposal to contextualize the study of movement in introductory courses of university physics, as a contribution to decision making in social situations. For this, the use of kinetic impact projectiles and the actual data provided by official sources are considered. This information is used in an object motion model describing the kinematic characteristics of a spherical projectile (a rubber bullet). For these purposes, a Reynolds number Re ≫ 1 was used, which allows one to apply a nonlinear motion equation to find the velocity and impact energy per unit area of a projectile. The results and analysis of this model can generate an interesting discussion in the classroom about the need to build protocols for the use of kinetic impact projectiles, and the importance of using scientific knowledge in social conflicts. © 2020 European Physical Society.